The role of game preferences on arousal state when playing first-person shooters - Suvi K. Holm; Johanna K. Kaakinen; Santtu Forsström; Veikko Surakka (Germany, 2022)
Several player typologies have emerged as a result of needing to understand
the role of personal preferences when selecting and playing games.
However, experimental investigations into whether these preferences affect psychophysiological
responses when playing have been scarce. In this study, two
groups of active gamers (N=24) played and watched a gameplay video of a firstperson
shooter game. The two groups consisted of players who either preferred
or disliked game dynamics prominent in first-person shooter games, such as killing
and shooting. While playing and watching, the participants’ electrodermal
activity and heart rate were monitored as indexes of autonomic arousal. The results
suggest that playing preferences and autonomic arousal are related. Those
who preferred the content showed a stable arousal state across time when playing,
whereas those who disliked the content showed a rising tendency in autonomic
arousal state. The effects were similar when participants were watching a video
of gameplay.
GamiFIN Conference 2020. Proceedings of the 4th International GamiFIN Conference Levi, Finland, April 1-3, 2020